Necessary and sufficient conditions for two subclasses of analytic functions associated with Pascal distribution series
In the present paper, we determine necessary and sufficient condition for equation* Φ _q^m(z):=z-_n=2^∞ n+m-2m-1% q^n-1(1-q)^mz^n equation* whose coefficients are probabilities of Pascal distribution to be in the class H_T (β _1,β _1,… ,β _k;α ) of analytic functions with negative coefficients defined in the open unit disk. Further, we give necessary and sufficient condition for the integral operator G_q^mf(z)=_0^zΦ _q^m(t)tdt to be in the class G_T (β _1,β _1,… ,β _k;α ). , number=1, journal=Sarajevo Journal of Mathematics, author=Frasin, Basem Aref, year=2022, month=Mar., pages=37–44